Implementation of financial technology in local MSME on the economic development of Bali society - Permana, Dewa Gde Yoga; Wirayudha, I Gede Bayu (Universitas Negeri Yogyakarta, 2024)
Along with its development, the online offering business of one of Bali's local MSMEs has become an alternative in between busy work. With the obstacles faced by several business actors, especially in villages, the convenience provided by digitalization becomes a problem. Seeing the obstacles to payment from selling offerings online, a deep understanding of a transparent financial technology system is needed to make it easier and provide confidence to the Balinese Hindu community who carry out online banten ceremony transactions. This study aims to see the influence of Digital Financial Technology in increasing the development of local MSMEs and will automatically improve the community's economy. This research method uses descriptive analysis by looking at data on the growth of digital payment technology. The study results show evidence that local MSMEs are greatly helped by digital financial technology such as QRIS, virtual accounts, and e-wallets that can be accessed via smartphone. We cannot avoid digitalization, but we must be able to surf the fast wave of digitalization. With the many conveniences provided, it is hoped that the online offering business of one of Bali's local MSMEs can develop better and benefit the economy, especially the Hindu community in Bali.